An ubiquitous solution for advertising and loyalty purposes using NFC technology. (2017) - García, Gonzalo Cerruela; Ruiz, Irene Luque; Gómez-Nieto, Miguel Ángel
In this paper, we present an application based on near field communication (NFC) technology and oriented to advertising and user loyalty fields. The system combines NFC and in-air hand gestures with the purpose of creating an attractive leisure activity where customers are rewarded by shops with the possibility of obtaining a prize or discount on the purchases made. NFC is used for securing the participation of the user in the activity and for exchanging the prizes obtained. During the activity, users perform a fishing gesture (throwing and catching) with the mobile phone, simulating the capture of a prize that could be located anywhere in the shop. This gesture is recognised by mobile sensors. The tailoring of the system to specific business marketing strategies is also managed by the proposed solution.